FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MASYARAKAT DESA MELALUI PENGELOLAAN DANA DESA DI KECAMATAN PENEBEL - I NYOMAN WIDHYA ASTAWA; NI NYOMAN KASIH; NI PUTU RANI ARTINI (Universitas Mahasaraswati K. Mataram, 2023)
Community welfare can be realized through the success of economic development. Economic development is said to be successful if people's welfare increases. Community welfare includes a sense of security, there are public facilities that support the economy, income that encourages people's prosperity, and easy access to information. The purpose of this study is to analyze the effect of village characteristics, village economic development and village fund management on the welfare of the community in Penebel District. The method of determining the sample using non-probability sampling is purposive sampling method with a total sample of 54 respondents. The data collection method used a questionnaire with a Likert scale (5 scale). The data analysis technique used is path analysis. The results showed that village characteristics did not significantly affect the management of Village Funds in Penebel District, village economic development significantly affected the management of Village Funds in Penebel District, village characteristics and village economic development significantly affected the welfare of rural communities in Penebel District, Fund management The village has no significant effect on the welfare of the village community in Penebel District.